Feminist Perspectives on Domestic Violence in the Film Adaptation of It Ends with Us By Justin Baldoni - Purwarno, Purwarno; Erika Br Pa, Nabila Feby Feby; Zarfiana, Raissa Septy (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2025)
Domestic violence is a widespread social problem that disproportionately affects women and reflects deep-seated gender inequalities embedded in personal, cultural, and institutional structures. Feminist theory offers a critical lens for understanding how patriarchal norms and unequal power dynamics normalize abusive behavior while restricting victims’ access to justice and support. This study explores the feminist representation of domestic violence in the film It Ends with Us, adapted from Colleen Hoover’s bestselling novel, which has drawn significant attention for its portrayal of intimate partner abuse. Using a qualitative approach grounded in feminist criticism, the research examines the film’s depiction of physical violence, emotional manipulation, coercive control, and the psychological complexities faced by survivors. The narrative follows Lily Bloom, a woman trapped in a cycle of affection and harm, whose experiences highlight the intergenerational transmission of trauma and the lingering effects of witnessing violence in childhood. Her journey reflects the difficult process of asserting identity and agency within an abusive relationship. The analysis considers cinematic and narrative techniques such as framing, symbolism, dialogue, and character development to assess how the film shapes audience empathy and understanding. It also evaluates whether the film challenges or reinforces traditional gender roles and societal misconceptions surrounding domestic abuse. The findings suggest that It Ends with Us has meaningful potential to raise awareness, influence public conversation, and support feminist advocacy aimed at confronting patriarchal structures. Ultimately, the study argues that the film demonstrates the transformative capacity of feminist storytelling to encourage social reflection and empower survivors.